ANALISIS GAYA KEPEMIMPINAN PADA KELURAHAN SIDOREJO, KECAMATAN GODEAN KABUPATEN SLEMAN - Nooriskar, Meira Puja; Sujoko, Sujoko (Program Studi Manajemen Fakultas Ekonomi UST, 2025)
This research aims to examine the leadership style of the Head of Sidorejo Village, Godean District, Sleman Regency. The object of the research is the leadership style of the Head of Sidorejo Village. The problem addressed in this study is how the leadership style of the Head of Sidorejo Village is applied. This study uses a descriptive qualitative approach. Based on the research findings presented and developed in the discussion, it can be concluded that the leadership style of the Head of Sidorejo Village is reflected in his behavior in leading the daily governance at the Sidorejo Village Office. This leadership style encourages village officials to perform their responsibilities as public servants more effectively. This positive condition is created through cooperation between the village head and all village officials to achieve the organizational goals that have been set, both in accordance with the laws and government regulations that guide the governance of Sidorejo Village.